PEMIKIRAN DAN PENGARUH ETIKA DI ERA KONTEMPORER - Sulastryani Sulastryani; Mustari Mustafa; Muhaemin Latif (PIRSAP (Paser Institute for Scientific Research and Publications), 2024)
The contemporary era is marked by rapid technological advancements and social changes, which bring new challenges in the field of ethics. Traditional ethical thinking now has to adapt to the more complex modern context. In the digital and global environment, issues such as privacy, human rights, sustainability, and artificial intelligence have become the main focus of ethical discussions. This research examines how ethical concepts are applied in the contemporary era, as well as the thoughts and influences of ethics in this period.